PENERAPAN NATURAL LANGUAGE PROCESSING PADA PENGELOLAAN BERKAS DIGITAL MENGGUNAKAN CHATBOT DI PUSDATIN DINAS PPKUKM - Bagus Tri Mahardika; Rezza Maulana (Prodi Teknologi Informasi Universitas Darma Persada, 2025)
Digital document management is a significant challenge for government organizations, particularly when the information retrieval procedure remains manual and inefficient. This research seeks to create a chatbot system utilizing Natural Language Processing (NLP) to aid users in locating and reading digital files through natural language instructions. This system was deployed at the Data Center (Pusdatin) of the PPKUKM Office to expedite information retrieval and enhance document management efficiency. The system was constructed utilizing the Laravel framework for the user interface and Python's FastAPI for natural language processing. Features encompass document retrieval by name and date, along with the capability to exhibit document content directly. This research utilized the Waterfall software development methodology, encompassing stages of requirements analysis, system design, implementation, and testing. The final results indicate that the system operates effectively and offers a more adaptable and user-centric interaction experience.